Research on Bovine Endometritis: Current Insights and Future Directions – A Review - Singh , Madhumeet (The Indian Journal of Animal Reproduction, 2023)
The post-partum reproductive performance of cows is identified as a pivotal factor influencing the success or failure  of the dairy industry. Achieving timely uterine involution, complete endometrial regeneration, and the resumption of  ovarian cyclic activity are crucial for conception within the desired timeframe. However, uterine contamination with  pathogens during parturition remains an unavoidable challenge, leading to suboptimal productivity and fertility. Metritis  and clinical endometritis are recognized post-partum conditions, while sub-clinical endometritis has emerged as a  significant threat to achieving desired fertility in dairy cows. This review summarizes a comprehensive assessment of  factors contributing to delayed clearance and persistence of uterine infections in dairy cows, particularly sub-clinical  endometritis (SCE). Diagnostic techniques, including bacterial culture, the Whiteside test, endometrial cytology, and  trans-rectal ultrasonography (TRUS), are discussed, each with advantages and limitations.The paper explores the  association between SCE and various risk factors, such as negative energy balance (NEB), metabolic indicators, and  hormonal changes during the post-partum period. The significance of parameters like body condition score (BCS), backfat  thickness (BFT), and metabolic indicators (leptin, NEFA, BHBA) in assessing energy status and predicting reproductive  efficiency is highlighted.In addition, the underexplored area of fungal infections in dairy cows’ uteri, emphasizing fungi’s  opportunistic nature and their potential to cause reproductive failure has also been reviewed. The immune system’s role  in uterine defense against fungal infections and the diagnostic challenges, including mycological cultures and cytological  examinations, the therapeutic challenges, and the poor prognosis associated with fungal endometritis have also been  discussed.
Keywords: Subclinical endometritis; Fertility; Bovines; Pathogens